Er/Pr-codoped borotellurite glasses as efficient laser operated nonlinear optical materials - Narayana, Gandham Lakshmi; Kityk, Iwan V.; Mahdi, Mohd Adzir; Plucinski, Kazimierz Jerzy (Elsevier, 2018)
We have discovered a rare opportunity to operate by the SHG at fundamental wavelength 10.6 μm of microsecond CO2 laser during simultaneous irradiation by 1064/532 nm bicolor laser beams of (60-x-y)TeO2-10B2O3-10BaO-10ZnO-10Na2O-(x)Er2O3-(y)Pr6O11 (x = 0.5, 1.0; y = 0); (x = 0; y = 0.1, 0.2, 0.3, 0.4, 0.5); (x = 0.5,1.0; y = 0.1, 0.2, 0.3, 0.4, 0.5) (mol%) glasses. The effect has shown a drastic sensitivity of the effect to the Er/Pr ratio. The effect exists only during the simultaneous illumination and applied dc-electric field at 5 kV/cm. Only completely reversible changes were observed. The effect is a consequence of photopolarization during the bicolor coherent laser beams and its efficiency is determined by the transfer of excitation between the Er and Pr ions.